Efektivitas 5 Madzhab Teori Belajar (Behavioris, Kognitifistik, Konstruktifistik, Generatif, Dan Humanistik Untuk Penerapan Pembelajaran Bahasa Arab: The Effectiveness of 5 Learning Theory Schools (Behaviorism, Cognitivism, Constructivism, Generativism, and Humanism) for Implementing Arabic Language Learning - Chikmah, Khofshoh Roichanatul; Muniroh, Shofiyatu Zahrotil; Putri, Rika Triambarwati Diria; Bakar, M. Yunus Abu (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2023)
Islamic education is a learning process that prioritizes religious issues. In Islam, differences of opinion are inevitable. Just as in jurisprudence, which has four schools of thought, there are five schools of thought in learning theory in education. Each learning theory has its understanding, characteristics, principles, and learning steps, as well as advantages and disadvantages. This article contains data obtained using library research techniques, where data is collected from references such as books, journals, articles, and other types of readings. The data presented is a compilation of six schools of thought in learning theory. The data includes the understanding, characteristics, principles, and learning steps, as well as the advantages and disadvantages of each school of thought. Understanding the schools of thought in learning theory is crucial before conducting a learning process based on Islam. The influence of learning theory schools on student learning outcomes is significant because each school of thought has its way of educating its students. Therefore, this article enables prospective Islamic educators to understand the learning theories that will be applied to their students. Pendidikan Islam merupakan proses belajar yang mengedepankan masalah keagamaan. Dalam Islam tentu tidak jauh dengan perbedaan pendapat. Seperti halnya di dalam fiqih yang memiliki empat madzhab, dalam pendidikan juga terdapat lima madzhab teori belajar. Setiap teori belajar memiliki pengertian, ciri-ciri, prinsip-prinsip, langkah-langkah pembelajaran serta kelebihan dan kekurangan masing-masing. Artikel ini memuat data yang diambil menggunakan teknik library research yang mana data diambil dari referensi berupa buku, jurnal, artikel, dan jenis bacaan lainnya. Data yang dimuat merupakan saringan data mengenai enam madzhab teori belajar. Data tersebut berisi pengertian, ciri-ciri, prinsip-prinsip, langkah-langkah pembelajaran serta kelebihan dan kekurangan dari masing-masing madzhab. Madzhab teori belajar sangat penting untuk dipahami sebelum melaksanakan sebuah pembelajaran yang berdasarkan Islam. Pengaruh madzhab teori belajar terhadap hasil belajar siswa tentunya sangat besar karena setiap madzhab memiliki caranya tersendiri untuk mendidik siswanya. Maka dibuatnya artikel ini dengan tujuan agar para calon pendidik Islam memahami tentang teori belajar yang akan diterapkan kepada peserta didiknya.